The Rise of British Cultural Identity in Othello by Shakespeare - Ouattara, Dramane (European Scientific Journal, ESJ, 2020)
The rise of British cultural identity in Othello by Shakespeare stands as a special message to the non-native. It was a patriotic address Shakespeare intended for people who were not British and inhabited England of Queen Elizabeth the 1 st . The paper analysesthe foul and rude treatment of Elizabethan ways on the part of the people Shakespeare and the British community willingly accepted, then integrated into their society as an ordinal citizen. At the top of outraged British people, the preoccupation of Shakespeare with the issue of the rise of British cultural identity was illustrative than ever in his play. His hope and craving for a multi-cultural British society culminated in the societal project. The project was meant to campaign for the rise and promotion of a cultural identity typical of British ways and customs. In a word, the implementation of the societal project of the playwright would certainly allow British cultural identity to go up in value within the ongoing globalised world inclined to cultural homogenization of identities.